SLIDING WEAR CHARACTERISTICS OF BORON CARBIDE AND NOVEL SQUID QUILL ASH REINFORCED ALUMINIUM 6061 HYBRID COMPOSITES - N H, Padmaraj; G Keni , Laxmikant; K N, Chethan; Hegde , Sharun; IR , Nithin; Kumar, Anush; Mendon , Abhishek (Journal of Applied Engineering Science, 2022)
Reinforcement of metallic and non-metallic particulates will enhance or improve the tribological and mechanical properties of metal matrix composites. In the present study, Aluminium 6061 was reinforced with agro-waste based novel Squid Quill Ash (SQA) and Boron Carbide (B4C) by employing a stir casting process. Sliding wear behavior of Al/B4C/SQA hybrid composites investigated by varying SQA content (0.5%, 1%, and 1.5%), sliding speed (400,500 and 600 RPM), and applied load (10,20 and 30 N) using Pin on Disc apparatus. Experiments were performed based on Taguchi L27 orthogonal design. The role of control parameters on wear rate was estimated using the Analysis of variance method. Statastical analysis showed that applied load has a significant effect on the wear rate of the hybrid composites followed by SQA content and Sliding Speed. Material removal during wear test mainly due to the combined effect of formation of cracks, abrasion, and grooves on the target surfaces.
Keywords: squid quill, wear rate, hybrid composites, reinforcement, sliding distance